Noise Generators (A Review) - S. A. Vinokurov; V. N. Kochemasov; A. R. Safin (Известия высших учебных заведений России: Радиоэлектроника, 2023)
Introduction. At present, noise generators (noise signal generators) have a wide range of applications. For example, such devices can be used as sources of fluctuating interference when studying the limiting sensitivity of radio receivers and amplifying devices, as signal simulators of multi-channel communication equipment, as tools for measuring non-linear distortions and frequency characteristics of radio devices using spectrum analyzers with a constant bandwidth.Aim. Review of scientific achievements in the development of noise generators and their applications.Materials and methods. The material for analysis was collected using databases of scientific publications, online resources, and websites of noise generator manufacturers. The research spanned the timeframe of 60 years.Results. Various noise generators and their characteristics, currently available on the radio equipment market, are described. The analysis of their main technical characteristics is carried out; examples of their practical application are indicated.Conclusion. Noise signal generators are widely used in scientific research and are currently produced mainly by foreign companies. Domestic companies are poorly represented in this market, with little published information available. However, positive developments in this direction have recently been observed. Domestic manufacturers are launching R&D programs to develop noise signal generators, which could reduce dependence on imported products in the future